INTERACTION OF SCIENTIFIC SCHOOLS OF GRODNO UNIVERSITIES: FROM LASERS TO METAL NANOPARTICLES - Smotryn, S. M.; Anufrick, S. S.; Dovnar, R. I. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2025)
Background. In the 21st century, science is developing so quickly that it requires the scientist not only to work intensively, but also to develop new forms of cooperation. One of the options is interdisciplinary interaction, based on the continuity of the leadership of scientific schools of universities and the constant desire to develop mutually beneficial cooperation. The aim of the research is to show the effectiveness of interdisciplinary research of scientific schools of Grodno universities. Material and methods. We analyzed the effectiveness of cooperation between the scientific school of the Grodno State Medical University “Innovative technologies in the treatment of wounds and surgical infections” and the scientific school of Yanka Kupala State University of Grodno “Laser physics and coherent optics” from 1979 to 2025. Results. The analysis of cooperation of scientific schools of Grodno universities for a 45-year period showed that interdisciplinary interaction allows researchers not only to publish abstracts, conference materials, articles in local and international journals, implement joint grants, defend dissertations for the degrees of candidates and doctors of sciences, but also to offer new methods of treatment for practical application, protected by patents for inventions and instructions for use issued by the Ministry of Health of the Republic of Belarus. Together, this contributes to the significant development of Belarusian science and practice. Conclusions. Long-term cooperation of scientific schools is an effective tool for the development of science, especially in interdisciplinary research. It is especially effective at the present stage when developing new methods for the prevention and treatment of wound infection with a new approach to the use of laser technologies and the creation of wound coatings incorporating metal nanoparticles.